A reform agenda for UK construction education and practice. Issue 1 (21st August 2020) - Killip, Gavin
Achieving zero carbon requires major changes in buildings and construction practices, but both remain very hard to achieve. The UK construction sector operates in a low-skills equilibrium, whereby poor quality assurance and significant design–performance gaps accompany low educational attainment and low wages. Skills debates often focus too narrowly on the supply of skill, but consideration also needs to be given to skill demand and use in the workplace. An evaluation framework for zero-carbon construction is proposed in which types, orders, and domains of learning are explained and differentiated. Competence is presented as a bundle of learning attributes including theoretical knowledge, practical skill and integrity of character. Each type of learning operates in hierarchical orders and can apply in different domains: from the narrowest focus on individual tasks to broader domains of occupation and industry. This evaluation framework is used to analyse previous research with low-carbon pioneers, showing how higher orders of learning need to be applied on projects, in firms, networks and business models. If the construction industry is to achieve these levels of learning, and apply them regularly in mainstream practice, then fundamental changes are necessary to the structure of employment as well as educational reforms. Policy relevance: The UK construction sector currently operates in a low-skills equilibrium which negatively impacts the capabilities to produce low-energy buildings. Research with low-carbon pioneers shows how higher orders of learning need to be applied to projects, in firms, networks and business models. Higher levels of occupational competence should be the goal, combining theoretical knowledge, practical skill and quality of character (acting responsibly and with integrity). The achievement of higher level competences in mainstream practice will require significant changes to the structure of employment involving labour market reforms and higher levels of accreditation and professionalisation of construction vocations. Meaningful educational and training reform requires industry reform at the same time to create the appropriate demand pull.